Morphological and yield responses of 20 genotypes of bread wheat to drought stress - Jamali, Ali; Sohrabi, Yousef; Siose Mardeh, Adel; Hoseinpanahi, Farzad (Archives of Biological Sciences, 2020)
Paper description: • The wheat grain filling period usually experiences drought stress in Iran. • To study the yield of wheat grain, it is important to know which traits such as grain number and weight has a greater role in grain yield improvement. This relationship is different in different genotypes. • Twenty genotypes of wheat were examined in the Kermanshah region in order to identify high yield genotypes. • The quantitative traits screened herein can be used to improve grain yield of wheat genotypes in future breeding programs. Abstract: The aim of this study was to select wheat genotypes most resistant to drought stress. The experiment was conducted at the research farms of the Faculty of Agriculture, Kurdistan University, Sanandaj, Iran, during 2014-2015 and 2015-2016. A randomized complete block design with three replicates using 20 genotypes of rain-fed wheat was applied. Cluster analysis of different wheat genotypes segregated the genotypes into 3 groups. Comparison between the groups in the first crop year revealed that the second and third groups exhibited the highest rate of radiation-use efficiency (RUE), and the first group had the lowest. Grain yield was highest in the third group and lowest in the first group, with an average of 219.87 g/m2 and 173.40 g/m2, respectively. In the second crop year, the highest rate of RUE was reported in the first group and lowest in the second and third groups. The highest grain yield was observed in the second group and the lowest in the third group (315.40 g/m2 and 253.75 g/m2, respectively). Based on the results of the biplot, high-yield genotypes in the first year of cultivation included G14 (263.00 g/m2), G20 (264.50 g/m2), G18 (214.00 g/m2) and G19 (222.50 g/m2). Based on the results obtained by cluster and PCA analysis under stress conditions, we concluded that several traits play a role in determining the grain yield of wheat. https://doi.org/10.2298/ABS191128001J Received: November 28, 2019; Revised: December 17, 2019; Accepted: December 18, 2019; Published online: January 9, 2020 How to cite this article: Jamali A, Sohrabi Y, Siose Mardeh A, HoseinpanahiF. Morphological and yield responses of 20 genotypes of bread wheat to drought stress. Arch Biol Sci. 2020;72(1):71-9.